Phonological Addition and Deletion of Loan Words Used in Indonesian - Abdurrahim; Abdul Rahman; Bustani (PT. Penerbit Tiga Mutiara, 2024)
This study explores the phonological transformations that occur when foreign words, particularly English, are adopted into Indonesian. Employing a descriptive method, the research systematically examines how these words undergo changes and how their phonemes are altered during the adoption process. Using a linguistic approach combined with simple descriptive analysis, the study successfully analyzed a variety of borrowed words to uncover patterns in their phonological adaptation. The findings reveal that the adoption process often involves phonological addition, deletion, or retention of specific phonemes. Some phonemes remain constant, preserving their original sound, while others are either added or omitted to align with Indonesian phonological rules and linguistic norms. Notably, the study identifies and formulates about sixteen distinct patterns of phonological addition and deletion that regularly occur during this process. These patterns highlight the systematic nature of language adaptation, demonstrating how linguistic structures accommodate borrowed words to fit the phonological and phonetic framework of the target language. This research contributes valuable insights into the dynamic interaction between languages, particularly the way phonological structures are modified to ensure compatibility and ease of use in a new linguistic environment. These findings provide a foundational understanding of word adoption mechanics, enriching linguistic studies on loanwords and their impact on language evolution, particularly in Indonesian. The established formulas offer a structured perspective for further research in phonological adaptation and cross-linguistic influence.